If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(1) + -2y = -6 Multiply 3 * 1 3 + -2y = -6 Solving 3 + -2y = -6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2y = -6 + -3 Combine like terms: 3 + -3 = 0 0 + -2y = -6 + -3 -2y = -6 + -3 Combine like terms: -6 + -3 = -9 -2y = -9 Divide each side by '-2'. y = 4.5 Simplifying y = 4.5
| 2(1-e)=3e-8 | | -5(u-3)=-2u-3 | | 2.5*ln(x)-ln(2x)=0 | | 7n+5n=-12 | | 3/8w=5 | | 5w+4-9w-3= | | -6x=3y-1 | | 4x^6+9x^2-2=0 | | Cosx+senx=0 | | w=8+2.5T | | 3w+2=5(w+2) | | X/9=-52 | | (9x)/(7-6x)=15 | | -5(w-6)=-2w+24 | | 5+3*5-1=19 | | 5*x1/2=4 | | 511/2-223 | | 12-4m=6-3m | | 14/5=2x | | 8(0)+2y=-4 | | 4x=6(4.8) | | 11a+9b-2c= | | 8(1)+2y=-4 | | 9•1/3= | | 4y+25=-7(y+9) | | 12=2/5u | | 1.5x+8.4=2.5x | | 3.14/92.8 | | 0.16x=16+0.12x | | -3v+2=-10v-30 | | 1.5x+8.5=2.5x | | x+0.16=16+0.12x |